The most dangerous man in the country: Filinto Müller of Brazil - Rose, R. S. (Peter Lang Publishing, 2020)
Cuiaba Days -- A Young Man's Passion -- The Revolution of 1924 -- Exile and Return -- Vargas -- Police Chief -- The Estado Novo -- Limbo -- The CPI -- Senator -- A Row of Opinion.